CRTC3 links catecholamine signalling to energy balance - Song, Youngsup; Altarejos, Judith; Goodarzi, Mark O.; Inoue, Hiroshi; Guo, Xiuqing; Berdeaux, Rebecca; Kim, Jeong-Ho; Goode, Jason; Igata, Motoyuki; Paz, Jose C.; Hogan, Meghan F.; Singh, Pankaj K.; et al. (Nature (London), 2010)
The adipose-derived hormone leptin maintains energy balance in part through central nervous system-mediated increases in sympathetic outflow that enhance fat burning. Triggering of β-adrenergic receptors in adipocytes stimulates energy expenditure by cyclic AMP (cAMP)-dependent increases in lipolysis and fatty-acid oxidation. Although the mechanism is unclear, catecholamine signalling is thought to be disrupted in obesity, leading to the development of insulin resistance. Here we show that the cAMP response element binding (CREB) coactivator Crtc3 promotes obesity by attenuating β-adrenergic receptor signalling in adipose tissue. Crtc3 was activated in response to catecholamine signals, when it reduced adenyl cyclase activity by upregulating the expression of Rgs2 , a GTPase-activating protein that also inhibits adenyl cyclase activity. As a common human CRTC3 variant with increased transcriptional activity is associated with adiposity in two distinct Mexican-American cohorts, these results suggest that adipocyte CRTC3 may play a role in the development of obesity in humans. CRTC3 protein linked to obesity The cyclic-AMP-responsive protein Crtc3 (CREB-regulated transcription coactivator 3) is shown to promote obesity and insulin resistance in mice on high-fat diets by attenuating β-adrenergic receptor signalling in adipocytes. Crtc3 is expressed predominantly in adipose tissue; mice lacking Crtc3 are protected from the development of diet-induced obesity and remain insulin sensitive. This work suggests that Crtc3 may be an early signal in the development of obesity and perhaps also in type II diabetes. β-adrenergic receptor signalling in adipocytes stimulates energy expenditure via cAMP-dependent increases in lipolysis and fatty-acid oxidation, and this signalling mechanism is thought to be disrupted in obesity. Here, the cAMP-responsive CREB coactivator Crtc3 is shown to promote obesity in mice by attenuating β adrenergic receptor signalling in adipose tissue.